Flexible solar cells based on CdSe nanobelt/graphene Schottky junctions. Issue 17 (7th May 2015) - Gao, Zhiwei; Jin, Weifeng; Li, Yanping; Song, Qingjun; Wang, Yilun; Zhang, Kun; Wang, Suo; Dai, Lun
<x xml:space="preserve">Abstract</x> Flexible solar cells based on CdSe NB/graphene Schottky junctions are fabricated and evaluated under different bending conditions.